Narodziny nowej humanistyki z ducha gender - Dziamski, Grzegorz (Człowiek i Społeczeństwo, 2015)
If we accept the distinction between sex and gender, introduced by the Second Wave of Feminism, and if we agree that gender does not have to be limited to two sexes, we will enter the terrain of the queer, the world of labile, liquid sexuality where the borders between men and women get blurred and the space opens for creating various human hybrids. In Poland, the middle of 1990 saw the launch of the women’s studies, gay and lesbian studies, gender studies, queer, LGBT, opening new domains and new methods of human studies. We can call them post-feminist and cultural studies because they stem from the feminist distinction between sex and gender and are focused on gender, i.e. on cultural rather than biological determinants of human beings. The new human sciences will have to face such new narratives of human beings, rethink the concept of objectivity (science) and commitment, learn to live in pluralistic world of many theories and more precisely many discourses, and to learn to cooperate with various groups to present their point of view. But first of all, the new human sciences will have to replace the idea of unity by idea of difference. Once we were looking for unity, now we are looking for difference.